Pengaruh Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Divisi Online CV. Terang Indah Alpha Jakarta Barat - Ayu Amalia; H. Widhi Wicaksono (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the effect of work discipline and leadership on employee performance at CV. Terang Indah Alpha. This research uses quantitative methods with saturated sampling techniques, this study involved 25 respondents. The results of the analysis show that leadership has a significant effect on employee performance with a correlation coefficient of 0.634 and an influence contribution of 42.5%. Work discipline also has a significant effect with a correlation coefficient of 0.778 and an influence contribution of 60.5%. Simultaneously, leadership and work discipline have a significant effect on employee performance with a correlation coefficient of 0.605 and an influence contribution of 60.5%, while the rest is influenced by other factors. The results of hypothesis testing reinforce the finding that both variables have a strong and significant relationship to improving employee performance.